Influência do Deep Water Running na composição corporal, capacidade funcional e qualidade de vida e do sono em mulheres obesas: ensaio clínico randomizado - Pianna, Bruna (2018)
Introduction: Interval training in Deep water running (DWR-IT) is a training method to improve cardiovascular fitness, functional health and quality of life, contributing to control body weight. Its main advantage is the reduction of joint overload and a low risk of musculoskeletal injuries. Objective: To verify the effects of the DWR-IT program on body composition and functional capacity in overweight and obese middle-aged women. Methods: this is a controlled, open-label, two-arm clinical trial with stratified randomization. The volunteers were allocated in aquatic group (AG; n = 17), who were submitted to the intervention and control group (CG; n = 16), who were not submitted to any type of intervention. In both groups, electrical bioimpedance, six-minute walk test (6MWT), Chair Stand test (CST), Arm Curl test (ACT), Questionnaire on the Impact of Weight on Quality of Life-lite (IWQOL-Lite) and Food Frequency Questionnaires (FFQ), Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). The DWR-TI program lasted 12 weeks. Results: There was a reduction in abdominal circumference from 95.63 ± 8.87 cm to 92.44 ± 8.21 cm, an increase in functional capacity from 534.44 m ± 67.24 to 565.81 ± 49.25 m in the CST of 8.69 ± 2.18 repetitions for 12.50 ± 2.58 repetitions and in the ACT of 12.50 ± 3.83 repetitions for 17.63 ± 3.56 repetitions, there was improvement in the physical function of 37.81 ± 10.60 for 42.31 ± 9.87, improvement in subjective sleep quality from 1.00 (1.00 -2.00) to 1.00 (0.00 -1.00), duration of sleep 1.00 (0.75 - 2.00) to 0.50 (0.00 - 1.00) and in the overall score of 8.50 (6.00 - 9.25) to 5.00 (3.00 - 7.25) in ESS from 10.50 (3.75 - 14.25) to 8.50 (2.75 - 12.00) in AG. In CG there was a reduction in functional capacity from 533.13 ± 56.59 m to 504,13 ± 73.99 m and improvement in self-esteem from 27.03 ± 6.33 to 28.44 ± 6.67, in ESS of 9.50 (7.75 - 11.50) for 6.00 (2.75-9.75). Conclusion: The DWR-IT program was effective in reducing abdominal circumference, improvement in functional capacity, muscle strength and endurance, quality of life in obese women.